(untitled) (Research, Society and Development, 2022)
Sexual violence against children and adolescents is a public health problem that triggers several cognitive, behavioral, emotional and social damages. In this sense, the objective is identify the practices performed by psychology in the context of child and adolescent sexual violence, especially to highlight the psychosocial and physical consequences and investigate what strategies have been used by psychology to combat sexual abuse in children and adolescents. The present study is an integrative review in which productions from 2016 to 2021 in Portuguese, English and Spanish were analyzed. From the analysis of the 23 articles found, four thematic axes were verified: physical and psychological consequences caused by child sexual abuse, institutional childcare, psychology interventions against sexual abuse and psychology interventions in the family context. It was possible to verify the need for listening to cases of sexual violence, using interview techniques and ludic resources, to give voice to the experience of the child and adolescent. However, there are still limitations in the justice systems that make it difficult to offer a safe and welcoming space for this listening to take place. It is, therefore, up to psychology professionals to seek strategies to deal with such limitations and offer care practices.